Atropisomerism in 3-arylthiazolidine-2-thiones. A combined dynamic NMR and dynamic HPLC study. Issue 47 (10th November 2016) - Ciogli, A.; Vivek Kumar, S.; Mancinelli, M.; Mazzanti, A.; Perumal, S.; Severi, C.; Villani, C.
Abstract : Atropisomerism was observed on sterically hindered 3-arylthiazolidine-2-thiones, whose rotational energy barriers were measured using dynamic NMR and dynamic HPLC. Abstract : Sterically hindered 3-arylthiazolidine-2-thiones were prepared by a solvent-free reaction with arylisothiocyanates and 1, 4-dithiane-2, 5-diol. Atropisomerism was observed in two compounds (3 and4, aryl = 1-naphthyl and 2-methylnaphth-1-yl), whose rotational energy barriers were measured using dynamic NMR and dynamic HPLC. The experimental analyses were supported by DFT calculations. Thermally stable atropisomers were obtained by dehydration of compounds3 and4 and the absolute configuration of the atropisomers of compound6 was determined by theoretical simulation of the ECD and VCD spectra.